Microbiological study of neonatal septicemia with special reference to metallo-beta-lactamase producing pseudomonas aeruginosa - Varun Dwivedi; Ekta Agrawal; Ramanesh Murthy; Sagarika Pradhan (International Journal of Medical Research and Review, 2015)
Introduction: Metallo-beta-lactamase (MβL) producing Pseudomonas aeruginosa has emerged as a potential threat in cases of neonatal septicemia and poses great therapeutic challenge for physicians treating such infections. The emergence, selective multiplication & dissemination of antibacterial resistance are a serious global problem.Methods: This study was conducted with the objective to know the microbiological profile of neonatal septicemia cases and to examine the incidence of MβL producing strains among multidrug resistant (MDR) Pseudomonas aeruginosa from the suspected cases of neonatal sepsis between January 2012 – December 2014. A total of 994 cases admitted with the suspicion of neonatal sepsis were investigated. 295 (29.7%) isolates were obtained from the blood cultures of neonates. The isolates were identified and tested for the susceptibility to various antimicrobial agents.Results: Pseudomonas aeruginosa with 116 (48.3%) isolation among 240 Gram negative isolates was the predominant pathogen in our study. All the 74 (63.8%) multidrug resistant P. aeruginosa isolates were screened initially for Imipenem resistance, which were further tested for the presence of MβL by Imipenem-ethylene diamine tetraacetic acid (EDTA) disc method. MβL production was seen in 20 (71.4%) of the 28 Imipenem-resistant Pseudomonas aeruginosa isolates.Conclusion:It creates a great therapeutic problem as it may spread rapidly to various other species of Gram-negative bacilli. Therefore, to prevent the further spread of MβL producers, it is essential to rapidly detect MβL-positive isolates.